Epidemiological Factors in Patients with Endometrial Adenocarcinoma - Luis Enrique Pompa Montes de Oca; Johely López Rivas (Medisur)
Background: endometrial cancer is the most common gynecologic neoplasia and accounts for between 6 to 13 % of all cancers in women. Therefore, it becomes highly important to take into account the epidemiological factors related to endometrial cancer. Objective: to describe some of the epidemiological factors that appears in patients with endometrial adenocarcinoma. Method: an observational, retrospective and descriptive study of all patients treated at the "Enrique Cabrera" General Teaching Hospital with the diagnosis of endometrial cancer, n = 32, from January 1st, 2009 to December 1st, 2010 was conducted. Results: 68,7 % of patients were 60 years old or more, 50 % of them had 1 or 2 children, 75 % had their menarche before the age of 13 and 68,7 % began their menopause with 50 years old or more. As for chronic diseases, 75 % suffered from hypertension and 25 % from diabetes mellitus and ischemic heart disease. Conclusion: it is necessary to conduct a larger study including other risk factors in order to assess the true epidemiological factors of endometrial cancer that are present in our population.